Islamism, Blasphemy, and Public Order in Contemporary Indonesia - Peterson, Daniel (Universitas Islam Internasional Indonesia, 2024)
Public order has remained a central focus of successive Indonesian governments since independence. Since President Soeharto’s political demise in 1998, blasphemy and associated religious vigilantism have, at times, posed a serious threat to public order. Using several recent case studies, this article addresses that issue and argues that, insofar as Islamist actors, opportunistic politicians, and a complicit judiciary are permitted to use religion to disrupt public order and persecute those espousing minority beliefs, constitutional guarantees of the rule of law, legal certainty and equality before the law, citizenship, and other fundamental liberal democratic rights, will continue to be undermined in contemporary Indonesia.